Toward an Historical Understanding of Industrial Relations Theory in Canada - Murray, Gregor; Giles, Anthony (Relations industrielles / Industrial Relations, 1988)
In linking the discontinuities in the development of industrial relations theory in Canada with succeeding historical phases in the evolution of Canadian industrial relations, this article argues that an understanding of industrial relations theory must be historically grounded. It identifies four phases of theoretical development and suggests that the hold of Systems theory on the discipline should be understood as the product of a specific historical period which is now giving way to the emergence of new approaches.